Fundamentals of software engineering : 7th International Conference, FSEN 2017, Tehran, Iran, April 26-28, 2017, Revised selected papers /: 7th International Conference, FSEN 2017, Tehran, Iran, April 26-28, 2017, Revised selected papers. (2017) - Unknown
No abstract available